The Effect of Stretching on Reducing Lower Extremity Joint Pain in the Elderlies at the Binjai Elderly Service Unit - Youlanda Sari; Nurul Haflah; Susiana Kaban (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Pain is one of the main complaints that drives a person to come to health services. Aging is a natural process experienced by every living creature. The process includes several changes such as physiological, psychological, social and spiritual status. One of the causes of physiological changes in the musculoskeletal system is joint pain. There are several ways to overcome this, namely by practicing footwork (stretching). The aim of this study was to determine the effect of leg movement exercises (stretching) on reducing lower extremity joint pain in the elderly at the Elderly Care Service in Binjai. The type of research used in this research is pre-experimental design with a one group pre test-post test design. The population in this study was 52 elderly people aged 45-59 years. The samples in this study were 10 respondents in the treatment group and 10 respondents in the control group. The sampling technique used in this research is Non Probability Sampling, purposive sampling type. Data was taken using questionnaires and observation sheets. The variable is those who experience lower extremity joint pain. Next, the data were analyzed using a paired t-test with a significance level of p ≤ 0.05. The results showed a decrease in joint pain after giving exercise (stretching). The conclusion is that stretching reduces lower extremity joint pain in the elderly. By reducing joint pain, elderly people can become more active, productive and can live out their old age more comfortably. For future researchers, it is recommended that the scope of the research be deeper for more accurate results by involving a large sample, longer research time and stricter methods of controlling confounding factors. Keywords : Joint Pain, Middle age, Stretching